SRM index development and validation in Indian automobile sector. (2016) - Agariya, Arun Kumar; Singh, Deepali
The research paper proposes a reliable and valid supplier relationship management (SRM) index as a strategic tool specifically catering to Indian automobile sector. A standard methodology of scale development was followed to develop SRM scale and a case-based method was used to develop the index. SRM in Indian automobile sector emerged out to be a multi-dimensional construct comprising of trust, service quality, R'D and technological capability, flexibility, market orientation and support services. The literature in the area of SRM majorly deals with specific aspects of supply chain management like supplier selection, development and collaboration as well as purchasing strategy. But there is paucity of research pertaining to industry specific SRM index development and validation so as to get a holistic view. The strategic implications as well as marketing practitioners point of view is also discussed at the end for efficient and effective SRM practices by using SRM index.